N‐Heterocyclic‐Carbene‐Catalyzed Reaction of α‐Bromo‐α, β‐Unsaturated Aldehyde or α, β‐Dibromoaldehyde with Isatins: An Efficient Synthesis of Spirocyclic Oxindole–Dihydropyranones. Issue 2 (7th December 2012) - Yao, Changsheng; Xiao, Zhaoxin; Liu, Rui; Li, Tuanjie; Jiao, Weihui; Yu, Chenxia
<x xml:space="preserve">Abstract</x> Smooth as isatin! A straightforward synthesis of spirocyclic oxindole–dihydropyranones through an N‐heterocyclic‐carbene‐catalyzed [4+2] annulation of α‐bromo‐α, β‐unsaturated aldehydes or α, β‐dibromoaldehyde bearing γ‐H with isatin derivatives under mild reaction conditions is disclosed (see scheme). The concise construction, ready availability of the starting materials, avoidance of external oxidants, and the potential utilization value of final products in molecular biology and pharmacy makes this approach particularly attractive.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>